ANALYSIS OF THE INFLUENCE OF INFORMATION TECHNOLOGY AND INNOVATION ON STRATEGY AND COMPETITIVE ADVANTAGE OF INDONESIAN CULINARY SMES - Adi Daen Fahmi; Oktalisha Kirana Ulum; Hadi Supraktika (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Micro Small and Medium Enterprises (MSMEs) play an important role in the national and regional economies. With the advancement of the global economy and intensified market competition, the ability to innovate and integrate information technology has become crucial factors that can determine the survival and success of MSMEs. However, there are differing findings and practical implications that warrant further exploration through a comprehensive theoretical review of literature within a broader context. This study will comprehensively analyze the substantial impact of information technology capabilities and innovation on strategy development and competitive advantage in culinary micro, small, and medium enterprises in Indonesia. It seeks to incorporate findings from previous studies, assess the direct and indirect impacts of technology and innovation capabilities, and propose potential avenues for further research that could assist stakeholders in formulating effective strategies to improve competitiveness in global markets.